Socialization and Stengthening Management Organization Community Transformation in the Digital Era - Rundu Padang, Rikky; Tampubolon, Jonris; Muttiwijaya, Gede Teguh Prasetya; Ferdianto, Jemmy Regri; Putra, Made Pramana (JURNAL ABDIMAS MADUMA, 2025)
Digital transformation has become a necessity in the governance of community organizations in the digital era. The development of information and communication technology requires Community Organizations to carry out strategic adaptations in order to increase effectiveness, efficiency, and wider public participation. This study aims to examine the role of socialization in supporting the strengthening of digital transformation in the management of Community Organizations, as well as identifying challenges and strategies that can be implemented in the process. There were 60 participants involved in this activivity who come from different regions in Indonesia. The activity was conducted online through Zoom Conference. The results of the community service show that socialization carried out continuously through various digital platforms can increase digital literacy of members, encourage collaboration between institutions, and strengthen organizational transparency and accountability. In addition, successful digital transformation is supported by visionary leadership, the availability of technological infrastructure, and adaptive regulatory support. However, the main challenges faced include resistance to change, gaps in HR capacity, and budget constraints. Therefore, a strengthening strategy is needed through digital training, increasing multi-sector partnerships, and establishing an inclusive digital ecosystem for Community Organizations. The conclusion of this Community Service is that socialization and strengthening of digital-based management are the keys to success in realizing relevant, responsive, and highly competitive Community Organizations in the digital era. Keywords: Digital Transformation, Community Organizations, Socialization, Institutional Strengthening, Digital Era